(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2014)
The Tijuana River Watershed is trans-border river basin flowing across the westerly portion of the US-Mexico border to the Pacific Ocean. This cross border region, a portal through which over 50 million people passes each year and the busiest land-border crossing in the world, is a place of contradiction and contested interests, a place known for extreme poverty, crime and violence as well as intense artistic and cultural production. At the same time, Tijuana is a social laboratory that has emerged out of the intense clash of cultures and the immense flow of people and ideas across the border.